Geodynamics - Turcotte, Donald Lawson; Schubert, Gerald (Cambridge : Cambridge University Press, 2014)
Essential reading for any Earth scientist, this classic textbook has been providing advanced undergraduate and graduate students with the fundamentals needed to develop a quantitative understanding of the physical processes of the solid earth for over thirty years. This third edition has two completely new chapters covering numerical modelling and geophysical MATLAB® applications, and the text is now supported by a suite of online MATLAB® codes that will enable students to grasp the practical aspects of computational modelling. The book has been brought fully up to date with the inclusion of new material on planetary geophysics and other cutting edge topics. Exercises within the text allow students to put the theory into practice as they progress through each chapter and carefully selected further reading sections guide and encourage them to delve deeper into topics of interest. Answers to problems available within the book and also online, for self-testing, complete the textbook package.
Title from publisher's bibliographic system (viewed on 29 May 2018).
Keywords: elektronické knihy; electronic books; Geodynamics